Fundamentalist Movement in Islamic Universities (Study: Movement Patterns and Cadreization Strategy of Hizbut Tahrir Indonesia at UIN Syarif Hidayatullah Campus, Jakarta) - Akhmad Haris Khariri (The International Journal of Politics and Sociology Research, 2021)
The purpose of this study was to determine the pattern of movement and regeneration strategies developed by HTI and to find out the symptoms of Islamic fundamentalism at the UIN Jakarta campus. This research was conducted through library research and interviews. The author found that the movement patterns and strategies of HTI regeneration in the UIN Jakarta campus were relatively intense and took several forms, including by utilizing various facilities, both internally owned by the organization and campus facilities, such as using campus media, Radio Da'wah and Communication RDK, Faculty of Da'wah and Communication. , SC Student Center worship facilities, affiliation with the Student Executive Board (BEM) and others. As for the internal means of HTI developing organizational resources such as the development of study groups such as SRIKAYA, Echoes of Liberation, Muslim Science Community MSC, Lisma HTI and others. The coaching process is taken through various stages such as the stage of coaching and cadre (al-tathqif), the stage of interacting with the people (marhalah al-tafaul ma'a al-umah), and the stage of taking power (istilam al-hukm). Furthermore, related to Islamic fundamentalism, the author finds some similarities in the characteristics of HTI with the Islamic fundamentalism movement, such as HTI's attitude in responding to Western ideas, having strong political elements, ways of understanding religious doctrine and others. This argument is formulated through an analysis stage, namely by looking at the symptoms of HTI growth and analyzing the various activities carried out by activists and the HTI regeneration process at the UIN Jakarta campus. Besides that, The author tries to link several indicators attached to HTI with the characteristics of fundamentalism that have been classified by experts. The theoretical framework used in this thesis is Islamic fundamentalism, social movement theory and strategy theory.